Mechanical properties of 3D-printed pentadiamond. (23rd September 2022) - Felix, Levi C; Ambekar, Rushikesh S; Woellner, Cristiano F; Kushwaha, Brijesh; Pal, Varinder; Tiwary, Chandra S; Galvao, Douglas S
Abstract: In this work, we combined fully atomistic molecular dynamics and finite elements simulations with mechanical testings to investigate the mechanical behavior of atomic and 3D-printed models of pentadiamond. Pentadiamond is a recently proposed new carbon allotrope, which is composed of a covalent network of pentagonal rings. Our results showed that the stress–strain (SS) behavior is almost scale-independent. The SS curves of the 3D-printed structures exhibit three characteristic regions. For low-strain values, this first region presents a non-linear behavior close to zero, followed by a well-defined linear behavior. The second regime is a quasi-plastic one and the third one is densification followed by structural failures (fracture). Young's modulus values decrease from 520 to 486 MPa. The deformation mechanism is bending-dominated and different from the layer-by-layer deformation mechanism observed for other 3D-printed structures. They exhibit good energy absorption capabilities (3.5 MJ kg −1 ), with some structures even outperforming epoxy Kevlar and TRIP-steel. The structures show better absorption potential than the well-known porous architectures such as honeycomb, schwarzites, and tubulanes and occupy the same region of woven structures in the Ashby chart.